Applying theory of planned behavior to predict exercise maintenance in sarcopenic elderly - Ahmad MH; Shahar S; Teng NIMF; Manaf ZA; Sakian NIM; Omar B (Clinical Interventions in Aging, 2014)
Mohamad Hasnan Ahmad,1 Suzana Shahar,2 Nur Islami Mohd Fahmi Teng,2 Zahara Abdul Manaf,2 Noor Ibrahim Mohd Sakian,3 Baharudin Omar41Centre of Nutrition Epidemiology Research, Institute of Public Health, Ministry of Health, Kuala Lumpur, Malaysia; 2Dietetics Program, 3Occupational Therapy Program, 4Department of Biomedical Sciences, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia Abstract: This study aimed to determine the factors associated with exercise behavior based on the theory of planned behavior (TPB) among the sarcopenic elderly people in Cheras, Kuala Lumpur. A total of 65 subjects with mean ages of 67.5±5.2 (men) and 66.1±5.1 (women) years participated in this study. Subjects were divided into two groups: 1) exercise group (n=34; 25 men, nine women); and 2) the control group (n=31; 22 men, nine women). Structural equation modeling, based on TPB components, was applied to determine specific factors that most contribute to and predict actual behavior toward exercise. Based on the TPB’s model, attitude (ß=0.60) and perceived behavioral control (ß=0.24) were the major predictors of intention to exercise among men at the baseline. Among women, the subjective norm (ß=0.82) was the major predictor of intention to perform the exercise at the baseline. After 12 weeks, attitude (men’s, ß=0.68; women’s, ß=0.24) and subjective norm (men’s, ß=0.12; women’s, ß=0.87) were the predictors of the intention to perform the exercise. “Feels healthier with exercise” was the specific factor to improve the intention to perform and to maintain exercise behavior in men (ß=0.36) and women (ß=0.49). “Not motivated to perform exercise” was the main barrier among men’s intention to exercise. The intention to perform the exercise was able to predict actual behavior regarding exercise at the baseline and at 12 weeks of an intervention program. As a conclusion, TPB is a useful model to determine and to predict maintenance of exercise in the sarcopenic elderly.Keywords: theory planned behavior, aging, elderly, sarcopenic, exercise